Assessment of body work condition by RULA method in a motor vehicle industry in order to design an effective exoskeleton system - M Bahrami; V Choopankareh; H Sadeghi Naiini; F Dayani (Salāmat-i kār-i Īrān, 2012)
Background and aims : physical activities in occupations like handling, static and dynamic postures, sudden movements, and repetitive postures are amongst most important risk factors of Work related Musculoskeletal Disorders (WMSDs). There are many ergonomic methods for assessing WMSDs which can be used in different cases, but these assessments and analyses can not be beneficial by themselves and should be promoted with usable, practical suggestions to improve the work condition. Such quality is brought to this research paper by first assessing ergonomic risks level, resulted by postural stresses, with special emphasis on improper postures, forces and repeating and then using these information to design assisting device called exoskeleton for improving work condition and industrial tasks.   Methods: For assessing and analyzing upper body work condition, postures in 17 different tasks were analyzed by RULA (Rapid upper limb assessment) method and a set of 60 worksheets were created out of them. Also biomechanical movement observation during normal tasks was done. Then HONDA company`s exoskeleton for lower body was analyzed and some design elements were extracted from it, to design an upper body exoskeleton based on the same design language.   Results: This Research shows that none of tasks were completely acceptable, and neck, trunk and legs were more affected by improper postures. There was no meaningful difference between right and left hand conditions in overall task and posture assessment. Research also shows dominant effect of force and repeat risk factors in tasks being harmful for upper body. Analyzing HONDA company`s exoskeleton shows the likelihood of success in upper body exoskeleton for improving work conditions and minimizing WMSDs.   Conclusion: Although redistribution or regular rotation of personnel, changing and optimizing work cycles and proper training might reduce WMSDs and improve work condition, but using an assisting device such as exoskeleton can minimize WMSDs and have a more desirable effect from ergonomic and physiological perspectives. Assisting devices like HONDA company`s lower body assisting exoskeleton have clearly shown the statement to be true.